Aspergillus ibericus lipase production by solid-state fermentation of olive pomace - Oliveira, Felisbela Maria Araújo (2015)
Lipases are versatile catalysts with many applications, such as in food and detergents industries. Lipases can be produced by solid-state fermentation (SSF) using agroindustrial wastes. In addition, A. ibericus has been pointed as an interesting fungus to produce lipase through SSF of olive pomace (OP). The aim of this work was to optimize the production of lipase by A. ibericus under SSF using OP and wheat bran (WB). Additionally, extraction conditions of lipase were optimized. At optimum conditions lipase production and recovery improved 2-fold, yielding 223 ± 5 U/g. Optimum SSF conditions were using 30 g in a ratio of 1:1 (dry basis) of OP and WB supplemented with 0.4 g (NH4)2SO4 at 60% of moisture content and incubated at 30 ºC during 7 days. The extraction of lipase was improved using 7.5 mL/g solid residues of 1% Triton X-100 homogenized for 0.5 hour at 250 rpm and 24 ºC.